Exámen especial a los elementos de propiedad, planta y equipo de la camaronera Camarada S.A en el período 2019. - Gomez Valarezo, Denisse Katherine (My University, 2020)
This analysis makes reference to the control and measurement of property, plant and equipment and how the company controls and records in the statement of financial position, governed by the parameters established by IAS 16. The special examination of property elements , plant and equipment, focuses on knowing how to evaluate? The internal control of long-lived assets. IAS 16 fundamentally seeks to standardize the treatment of this component of financial statements, so that information about the investment made by companies and the changes that occur in said investment in property, plant and equipment can be recognized. The value of the goods can cover a significant percentage very within the assets and memorandum accounts, which demands that its control be assumed with great responsibility by all the members of a company; that is, from the highest authority mainly, custodians, and all servers. Verify the existence and application of a control policy for the accounting management of plant and equipment properties in the camaronera CAMARADA SA, determining that adequate records are kept that allow the correct classification of the same according to their characteristics, such as control timely use and disposal. Carrying out the applicable audit procedures according to the circumstances, through the preparation of reports of the results obtained where the strength or weaknesses of internal control are reflected..
El presente análisis hace mención al control y la medición de la propiedad planta y equipo y de como la empresa los controla y registra en el estado de situación financiera, regidos en el parámetros que establece la NIC 16. El examen especial a los elementos de propiedad, planta y equipo, se enfoca en conocer ¿cómo evaluar? El control interno de los bienes de larga duración. La NIC 16 busca fundamentalmente estandarizar el tratamiento de este componente de los estados financieros, a fin de que se pueda reconocer la información acerca de la inversión que realizan las empresas y los cambios que se producen en dicha inversión en propiedades, planta y equipo. El valor de los bienes puede cubrir un porcentaje muy significativo dentro de los activos y cuentas de orden, lo que demanda que su control sea asumido con mucha responsabilidad por todos los miembros de una empresa; esto es, desde la máxima autoridad principalmente, custodios, y todos los servidores. Verificar la existencia y aplicación de una política de control para el manejo contable de las propiedades planta y equipo en la camaronera CAMARADA S.A, determinando que se mantengan los registros adecuados que permitan la correcta clasificación de los mismos de acuerdo con sus características, como el control oportuno de su uso y disposición. Realizando los procedimientos de auditoria aplicables de acuerdo a las circunstancias, mediante la elaboración de informes de los resultados obtenidos dónde se reflejen la solidez o debilidades del control interno.
Keywords: CONTROL INTERNO; EVALUACIÓN; BIENES; RIESGO DE CONTROL